2019
DOI: 10.1111/jam.14280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold plasma, UV‐C or aqueous ozone treatment on Botrytis cinerea and their potential application in preserving blueberry

Abstract: Aims This study aimed to compare the effects of cold plasma (CP), ultraviolet (UV‐C) and aqueous ozone (AO) on Botrytis cinerea and explore their application in preserving blueberry. Methods and Results The effects of CP, UV‐C or AO on B. cinerea were investigated. Results showed that three treatments effectively inhibited the growth of B. cinerea, increasing cell membrane penetrability and causing the leakage of cytoplasm and nucleic acid. Scanning electron microscopy showed that CP caused the mycelium fold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…Their results indicated that compared with control, PAW treatments for different times (5, 10, and 15 min) followed by storage for 7 days elevated the contents of SOD. In addition, Zhou et al (2019) reported that both UV-C and aqueous ozone as well as cold plasma treatment elevated the activity of SOD and CAT in blueberries, but a gradual decrease was observed after posttreatment storage for a few days, and compared with UV-C and aqueous ozone treatments, cold plasma exposure displayed better preservation effects on blueberries. Similar results were reported by Puač et al (2014) in carrot calli.…”
Section: Endogenous Enzymes Inactivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results indicated that compared with control, PAW treatments for different times (5, 10, and 15 min) followed by storage for 7 days elevated the contents of SOD. In addition, Zhou et al (2019) reported that both UV-C and aqueous ozone as well as cold plasma treatment elevated the activity of SOD and CAT in blueberries, but a gradual decrease was observed after posttreatment storage for a few days, and compared with UV-C and aqueous ozone treatments, cold plasma exposure displayed better preservation effects on blueberries. Similar results were reported by Puač et al (2014) in carrot calli.…”
Section: Endogenous Enzymes Inactivationmentioning
confidence: 99%
“…In addition, compared with UV‐C and aqueous ozone treatments, Zhou et al. () reported that cold plasma exposure was more effective in inhibiting the growth of Botrytis cinerea and thus had better preservation effect on blueberries. Interestingly, cold plasma had the advantages in in‐package sterilization because reactive species can be generated directly inside a sealed package with no postprocess contamination (Zhuang et al., ).…”
Section: Applications For Shelf Life Extensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al 2019reported similar findings when blueberries were treated with gas plasma and exhibited less discoloration compared to nontreated controls. It was proposed that the exposure of blueberries to reactive oxygen species stimulated oxidative stress enzymes that provided protection against oxidation reactions during storage (Zhou et al, 2019). The same effect could have occurred in grapes but regardless of this fact, illustrates the advantage of AOP over that of applying UV-C or hydrogen peroxide alone.…”
mentioning
confidence: 99%